Pay Attention to Inattention: Exploring ADHD Symptoms in a Sample of Underachieving Gifted Students. (April 2020) - McCoach, D. Betsy; Siegle, Del; Rubenstein, Lisa DaVia
Much has been written about the relationship of giftedness and attention-deficit/hyperactivity disorder (ADHD), as well as the relationship between ADHD and underachievement. The present study examined whether students who were identified as gifted underachievers were more likely to manifest symptoms of ADHD, as measured by the ADHD-IV. Over half of the gifted underachievers met the screening criteria for ADHD based on teacher reports, and almost 30% of the gifted underachievers met the screening criteria for ADHD based on parent reports. Most of these students had elevated scores on the inattention scale. The prevalence of inattention was over 2 times as high as the prevalence in the norming sample using the teacher rating scales and over 5 times as high as the prevalence in the norming sample using the parent rating scales. Although parents and teachers rated students similarly on the hyperactivity scale, teachers rated students as more inattentive than parents did. However, elevated parent ratings of inattention negatively predicted students' self-regulation, goal valuation, and self-efficacy. Self-regulation was most strongly related to inattention. We cannot know whether the gifted underachievers with high inattention scores have undiagnosed ADHD. However, our results suggest that a substantial percentage of gifted underachievers exhibit attentional problems at home, and that these attentional problems are severe enough to merit further examination.